"Witch" and "Shaman": Discourse Analysis of the Use of Indigenizing Terms in Italy. (16th November 2018) - Puca, Angela
Abstract : From the very birth of the term, Strega ("Witch") has been used with a negative connotation to describe women with powers aimed at harming people. Strega has its etymological origin in the Latin Strix, the owl believed to feed on human blood. Pop culture, books and media alike, also portrayed the witch as an evil character to the point where it became common parlance to address a person deemed evil as a witch. In the last three decades, with the popularization of paganism and Wicca, the term has been reclaimed and somehow sanitized by Pagans who neutrally describe this figure as someone who has the ability to change reality in accordance with the will. In more recent years, with the spread of shamanism, more practitioners start to either renounce the term "witch" in favour of Sciamano/sciamana ("Shaman") or use them both to define themselves. By analysing the discourses that practitioners create around the terms "witch" and "shaman"by means of Paul Johnson's categories, I will illustrate how both terms manifest a form of indigenization and extending. In conclusion, I will argue that indigenizing and extending may be seen as two aspects of the same phenomenon entailing the opening of cultural borders to the outside, reshaping both the imported and exported cultural elements.